2007
DOI: 10.4103/0971-6203.35720
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation methods for detecting changes in beam output and energy in radiation beams from high-energy linear accelerators

Abstract: There is need for simple methods for checking consistency of beam outputs and energy in linear accelerators used for radiotherapy. A method was designed by the department using perspex phantom with which the dosimetric data of two medical linear accelerators (Clinac 600 CD, Clinac 2300 CD) were evaluated over a period of 30 months. The efficacy of methods followed was checked. Routine beam consistency checks were designed for photon beams with 15 cm/ 5 cm depth ionizations in perspex phantom and variable depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…An earlier report [14] highlighted the efficacy of using ratios of ionization in perspex as a measure of photon beam qualities for 6 and 15 MV. In Table 3 it is observed that as the FSD changed from 2 m to 4 m, the ionization ratios for depths 20/15 and 25/15 in phantom showed slight variations in a progressively decreasing manner.…”
Section: Discussionmentioning
confidence: 98%
“…An earlier report [14] highlighted the efficacy of using ratios of ionization in perspex as a measure of photon beam qualities for 6 and 15 MV. In Table 3 it is observed that as the FSD changed from 2 m to 4 m, the ionization ratios for depths 20/15 and 25/15 in phantom showed slight variations in a progressively decreasing manner.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore in the year 2008 only first TL postal dose intercomparison was possible. However, beam output and energy stability have been evaluated since patient treatment with linacs began in 2005, and have been documented in a previous report[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The method of maintaining a constant cGy/MU in our linac photon and electron beams was explained in a previous report. [ 2 ] When the daily check of output/MU showed drift beyond ±2% limits retuning is carried out by the local service personnel. [ 2 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations